Efficacy of Dwitiya Baladi Basti and Shaman Chikitsa as an Analgesic in the Management of Katigraha (Low Back Pain). - Aggarwal, Vishal; Gupta, Arun (International Research Journal of Ayurveda & Yoga, 2023)
Background: Back Pain is the remarkably common disability around the world. Despite its frequency, backache is not a dramatic disease that arouses scientific curiosity and interest to the practitioners. Here an attempt has been made to evaluate the analgesic effect of Basti Chikitsa (Ayurvedic Enema therapy) in the patients with Katigraha (Chronic low back pain) Aim: We aimed to evaluate the Rujahara (Analgesic) Effect of Dwitiya Baladi Yapana Basti in Comparison to Ayurvedic Medication (Tryodashanga Gugglu and Rasnadi Kwath) in the Management of Katigraha (Low Back Pain). Materials and Methods: This study was conducted on 60 clinically diagnosed cases of Katigraha (Low Back Pain) from OPD of Ch. Brahm Prakash Ayurved Charak Sansthan, Khera Dabar, Najafgarh, New Delhi in a period of 12 months after taking institutional ethical clearance. Parameters to evaluate the analgesic effect were Oswestry’s disability index (ODI) as subjective parameter and Visual Analouge scale, Kemp’s test as objective parameters. Participants were divided into two groups: Group A – Dwitiya Baladi Yapana Basti was given and in Group B- Tryodashanga Gugglu and Rasnadi Kwath were given. Results: A significant difference was found between two groups in objective parameters. In Group A there was a relief of 29.8% in ODI Scale, VAS Scale 33.1% and Kemp’s test -65.2 % whereas in Group B there was a relief of 33.1% ODI scale, VAS Scale-22.4% and Kemp’s test- 36.8%. Conclusion: Both the group showed mild to moderate relief in the management of Katigraha. Both the group are equally effective in reducing the Ruja (pain) in Katigraha but Basti Karma showed more relief in objective parameters. No major adverse or side effect were encountered during the course of study.